2002
DOI: 10.1097/00006123-200210000-00035
|View full text |Cite
|
Sign up to set email alerts
|

Transplanted Neural Stem Cells Survive, Differentiate, and Improve Neurological Motor Function after Experimental Traumatic Brain Injury

Abstract: These data suggest that transplanted NSCs can survive in the traumatically injured brain, differentiate into neurons and/or glia, and attenuate motor dysfunction after traumatic brain injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
93
0
2

Year Published

2007
2007
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 138 publications
(100 citation statements)
references
References 46 publications
5
93
0
2
Order By: Relevance
“…We also tested different post-injury time points for transplantation, and found that grafting at 2 days post-injury had better cell survival compared to transplantation at 7 or 14 days post-injury (data not included). The results are similar to some from previously reported studies using other cell sources (Boockvar et al, 2005;Riess et al, 2002). Using the stereological cell quantification method, we determined the remaining number of transplanted cells at 2 and 4 weeks following transplantation, and found around 46% of total injected cells and 36% in the injured brain, respectively, and 48% and 39% in the sham brain, respectively.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…We also tested different post-injury time points for transplantation, and found that grafting at 2 days post-injury had better cell survival compared to transplantation at 7 or 14 days post-injury (data not included). The results are similar to some from previously reported studies using other cell sources (Boockvar et al, 2005;Riess et al, 2002). Using the stereological cell quantification method, we determined the remaining number of transplanted cells at 2 and 4 weeks following transplantation, and found around 46% of total injected cells and 36% in the injured brain, respectively, and 48% and 39% in the sham brain, respectively.…”
Section: Discussionsupporting
confidence: 88%
“…However, what is unclear is which of these environments is more conducive for cell transplant survival. Within a different post-injury environment, published studies using cell sources ranging from embryonic murine (Boockvar et al, 2005;Hoane et al, 2004;Philips et al, 2001;Riess et al, 2002;Wallenquist et al, 2009), or fetal stem cell lines (Hagan et al, 2003;Shear et al, 2004;Tate et al, 2002Tate et al, , 2009Wennersten et al, 2004), to bone marrow cells (Mahmood et al, 2001a(Mahmood et al, , 2001b(Mahmood et al, , 2003Qu et al, 2009), have reported varying degrees of cell survival after transplantation into the injured brain, both at early and later post-injury time points. Many studies have indicated that post-injury timing and location of implantation are important factors determining the fate of transplanted NS/NPCs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar results were observed with fetal-derived NSCs overexpressing EGF receptor, when transplanted to the corpus callosum of CCI animals 49. These cells became mature neurons following transplantation into animals that showed significantly improved motor function, although cognitive dysfunction was unaffected 50. Alternately, improved cognition was observed when transplanted cells had been transduced with glial cell derived neurotrophic factor (GDNF), which showed an increased migration from the injury periphery 51.…”
Section: Tbi and Stem Cell Transplantationsupporting
confidence: 58%
“…However, stem cell therapies have offered some promise. Studies have shown that transplantation of neural stem cells provides neuroprotection after TBI (Riess et al 2002; Bakhtiary et al 2011; Arien-Zakay et al 2012; Wang et al 2013). Primarily through paracrine and endocrine mechanisms (Camussi et al 2010), stem cells regulate inflammatory response, decrease free radical production, reduce apoptosis, and promote endogenous neuronal growth, synaptic connections, and neural repair (Joyce et al 2010).…”
Section: Introductionmentioning
confidence: 99%